The Role of Movement and Gesture in Communicating Music Expressiveness to an Audience - An experiment on dynamics perception after a contemporary percussion performance. - Aroso,Nuno (2020)
Abstract Musical performative gestures are recognised by the majority of theoreticians as a critical factor of a musical performance. Gestures can be considered as operating features of a person’s perception-action system. It presupposes significance of a meaning that involves more than just a physical movement. Movements can be subdivided into specific patterns and conceptualised. Dynamics are one of the most relevant expressive element in music and they are strongly related to the physical musical action - sound producing gestures. Used effectively, dynamics allow sustain narrative pertinence in a musical performance, communicating for example a particular emotional state or feeling. For this research, solo percussion contemporary music performance was in focus and an audience divided in between “visual and non visual” listeners was studied. From this perspective, observation over percussionists’ playing manner and it ́s audience provides the researcher an opportunity to understand dynamics perception through musicians’ gestures in this particular repertoire. The quantitative research design divided in the experiment was chosen for the purpose of this study, which can be referred to as the description of the objective reality by using numbers in order to construct meaningful models reflecting various relationships between objects or phenomena. These numerical entities are not the reality itself, but a way of representing it. How does the percussive gesture influences the perception of musical dynamics by an audience?